2014
DOI: 10.1021/bi500205x
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Chemical Labeling of Mitochondrial Respiratory Complex I through Ligand-Directed Tosylate Chemistry

Abstract: The site-specific chemical modification of NADH-quinone oxidoreductase (complex I) by various functional probes such as fluorophores and microbeads, without affecting the enzyme activity, may allow single-molecule analyses of putative dynamic conformational changes in the enzyme. In an attempt to address this challenge, we performed site-specific alkynylation of complex I in bovine heart submitochondrial particles by means of a ligand-directed tosylate (LDT) chemistry strategy with synthetic acetogenin ligand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
138
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(154 citation statements)
references
References 43 publications
16
138
0
Order By: Relevance
“…Some molecular tags, such as fluorophore and biotin, can be covalently attached to the terminal acetylene via Cu +1 -catalyzed click chemistry following photoaffinity labeling, which enables purification and/or detection of the labeled peptides. 18) We confirmed that PRA1 and PRA2 maintain the potent inhibitory activities (Table 2), and are the most potent class in this study. Photoaffinity labeling experiments are currently under way in our laboratory using these photoreactive amilorides.…”
Section: Resultssupporting
confidence: 83%
“…Some molecular tags, such as fluorophore and biotin, can be covalently attached to the terminal acetylene via Cu +1 -catalyzed click chemistry following photoaffinity labeling, which enables purification and/or detection of the labeled peptides. 18) We confirmed that PRA1 and PRA2 maintain the potent inhibitory activities (Table 2), and are the most potent class in this study. Photoaffinity labeling experiments are currently under way in our laboratory using these photoreactive amilorides.…”
Section: Resultssupporting
confidence: 83%
“…Asp-139 resides on a four-helix bundle, which is known to be conformationally flexible based on structural and inhibitorbinding studies (12,23). A likely reason for the observed behavior is the abstraction of the proton from the Asp-139/His-38 ion pair that links to the Q reduction.…”
Section: Resultsmentioning
confidence: 99%
“…Alkynylated protein was identified and characterized using the Bruker Autoflex III 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 9 equipped with Ultimate 3000 nano-LC (LC-MS, Thermo Scientific), respectively, under the same experimental and data-processing conditions as those previously reported (15,16). 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 10…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…In order to visualize the incorporated alkyne, a fluorescent TAMRA-azido tag was conjugated with the alkyne via Cu +1 -catazyzed click chemistry (15). As shown in Figure 3, a fluorescent band was exclusively observed at ~50 kDa, indicating that the terminal alkyne was successfully transferred from AAT to the ~50 kDa protein.…”
Section: Specific Alkynylation Of Bovine Complex I Via Ldt Chemistrymentioning
confidence: 99%